Interações medicamentosas graves relacionadas às intoxicações por paracetamol - Okuyama, Julia Hiromi Hori; Lagemann, Letícia Mariano; Silva, Marcus Tolentino (Farmacoterapêutica, 2021)
Interações medicamentosas graves relacionadas às intoxicações por paracetamol.